Measuring the impact of COVID-19 social distancing measures on sexual health behaviours and access to HIV and sexual and reproductive health services for people living with HIV in Botswana - Ensor, Samuel; Mechie, Imogen; Ryan, Rebecca; Mussa, Aamirah; Bame, Bame; Tamuthiba, Lefhela; Moshashane, Neo; Morroni, Chelsea (Frontiers in Global Women's Health, 2023)
Introduction Uninterrupted access to HIV and sexual and reproductive health (SRH) services is essential, particularly in high HIV prevalence settings, to prevent unintended pregnancy and vertical HIV transmission. Understanding the challenges that COVID-19 and associated social distancing measures (SDMs) posed on health service access is imperative for future planning. Methods This cross-sectional study was conducted in Botswana between January–February 2021. A web-based questionnaire was disseminated on social media as part of the International Sexual Health and REproductive Health (I-SHARE) Survey. Respondents answered questions on SRH, before and during COVID-19 SDMs. Subgroup analysis and comparison of descriptive data was performed for people living with HIV (PLWH). Results Of 409 participants, 65 were PLWH (80% female, 20% male). During SDMs, PLWH found it more difficult to access condoms and treatment for HIV and STIs; attend HIV appointments; and maintain adherence to antiretroviral therapy. Compared to HIV-negative women, a higher proportion of women living with HIV used condoms as their primary method of contraception (54% vs. 48%), and had lower use of long-acting reversible contraception (8% vs. 14%) and dual contraception (8% vs. 16%). Discussion Mirroring global trends, COVID-19 disrupted HIV and SRH service access in Botswana. However, in high HIV-prevalence settings, disruption may more severely impact population health with disproportionate effects on women. Integration of HIV and SRH services could build health system capacity and resilience, reduce missed opportunities for delivering SRH services to PLWH and limit the consequences of future restrictions that may cause health system disruption